Ophidism in Lima - Pesce, Hugo (1956)
But there tanatofidios in the very capital of the Republic, it is not uncommon arrival at our hospitals subjects bitten by poisonous snakes, from places agrestres Department of Lima. While the overall causal data relates what the patient have a diagnosis of high importance gender causes and knowledge of appropriate therapy.